The complete mitochondrial genome of the cowpea weevil, Callosobruchus maculates (Coleoptera: Chrysomelidae: Bruchinae) and a related phylogenetic analysis of Chrysomelidae. Issue 2 (3rd July 2018) - Zhang, Li-Jie; Wu, Ling; Wei, Chun-Yan; Liu, Xing-Liang; Xue, Huai-Jun; Yang, Xing-Ke; Nie, Rui-E
Abstract: In this study, the complete 17, 809 bp mitochondrial genome of Callosobruchus maculates (F.) (Coleoptera: Chrysomelidae: Bruchinae) was sequenced using Illumina's HiSeq2000 platform. The mitogenome is a double-stranded circular molecule of 17, 809 bp in length with 21 transfer RNA genes, 13 protein-coding genes, and two ribosomal RNA genes as in other insects. Specially, there is a 2008 bp-inserted segment between ND2 and tRNA-Trp from 1180 to 3187, which cannot be aligned to any known gene of mitogenomes. To estimate the taxonomic status of Bruchinae, total 17 species from eight subfamilies of Chrysomelidae were selected as ingroups and three species of Lamiinae as outgroups for phylogenetic analysis based on mitogenome. The results showed that three major lineages were formed, including a basal 'Eumolpine' clade (Cassidinae, Eumolpinae, Cryptocephalinae, Clytrinae), ''Criocerine' clade (Criocerinae, Bruchinae) and 'Chrysomeline' clade (Chrysomelinae, Galerucinae s. l.). Bruchinae showed more closed relationship with Criocerinae than other subfamilies. More thorough taxon sampling will be needed to well understand the relationship in Chrysomelidae.